2016
DOI: 10.1148/radiol.2016152333
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Deaths in the National Lung Screening Trial Attributed to Nonsolid Nodules

Abstract: Purpose To validate the recommendation of performing annual follow-up of nonsolid nodules (NSNs) identified by computed tomographic (CT) screening for lung cancer, all cases of lung cancer manifesting as NSN in the National Lung Screening Trial (NLST) were reviewed. Materials and Methods Institutional review board and informed consent were waived for this study. The NLST database was searched to identify all participants with at least one NSN on CT scan with lung cancer as the cause of death (COD) documented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…For this report, the following definitions were used: Nonsolid nodules (NSNs): Nodules without a solid component that obscures the underlying lung parenchyma other than blood vessels [1, 2, 12] on thin-section CT scans (less than 1 mm) viewed on CT lung window settings. NSNs have also been called “ground-glass opacities (GGOs)”, “pure GGOs”, and “pure ground-glass nodules” [1518].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this report, the following definitions were used: Nonsolid nodules (NSNs): Nodules without a solid component that obscures the underlying lung parenchyma other than blood vessels [1, 2, 12] on thin-section CT scans (less than 1 mm) viewed on CT lung window settings. NSNs have also been called “ground-glass opacities (GGOs)”, “pure GGOs”, and “pure ground-glass nodules” [1518].…”
Section: Methodsmentioning
confidence: 99%
“…PSNs initially manifest as NSNs and later progress to develop internal solid components [1, 2, 4, 5]. PSNs have also been called “GGOs”, “mixed GGOs”,” mixed tumour with GGO”, “ground-glass nodules,” “mixed nodules,” “part-solid GGO”, “part-solid GGN”, and “partly solid or semisolid” [1518].…”
Section: Methodsmentioning
confidence: 99%
“…This was quickly accepted by the imaging community and incorporated into the current version of Lung-RADS as well as other authoritative guidelines (20,24) Another example relates to the management of nonsolid nodules where observation on an annual basis is now considered acceptable practice under certain conditions. Again, both the I-ELCAP database and NLST database have been used to confirm this approach (25,26). In the future, continued accrual of screening cases is needed in order to remain current with state-of-the-art technology.…”
Section: Role Of Registriesmentioning
confidence: 99%
“…The reports from lung cancer screening trials showed that conservative management of pGGN provides optimal balance between risk and benefits. In asymptomatic subjects at high risk of lung cancer, pGGN did not progress to advanced stage lung cancer in several years after first documentation on CT (29)(30)(31)(32). Therefore, long-term active surveillance by low-dose CT (LDCT) is encouraged until the evidence of nodule progression.…”
mentioning
confidence: 99%